Royal Free Hospital-Nutritional Prioritizing Tool improves the prediction of malnutrition risk outcomes in liver cirrhosis patients compared with Nutritional Risk Screening 2002 - Wu, Yuchao (Br J Nutr, 2020)
The European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines recommend the Royal Free Hospital-Nutritional Prioritizing Tool (RFH-NPT) to identify malnutrition risk in patients with liver disease. However, little is known about the application of the RFH-NPT to screen for the risk of malnutrition in China, where patients primarily suffer from hepatitis virus-related cirrhosis. A total of 155 cirrhosis patients without liver cancer or uncontrolled co-morbid illness were enrolled in this prospective study. We administered the Nutritional Risk Screening 2002 (NRS-2002), RFH-NPT, Malnutrition Universal Screening Tool (MUST) and Liver Disease Undernutrition Screening Tool (LDUST) to the patients within 24 h after admission and performed follow-up observations for 1·5 years. The RFH-NPT and NRS-2002 had higher sensitivities (64·8 and 52·4 %) and specificities (60 and 70 %) than the other tools with regard to screening for malnutrition risk in cirrhotic patients. The prevalence of nutritional risk was higher under the use of the RFH-NPT against the NRS-2002 (63 v. 51 %). The RFH-NPT tended more easily to detect malnutrition risk in patients with advanced Child–Pugh classes (B and C) and lower Model for End-stage Liver Disease scores (<15) compared with NRS-2002. RFH-NPT score was an independent predictive factor for mortality. Patients identified as being at high malnutrition risk with the RFH-NPT had a higher mortality rate than those at low risk; the same result was not obtained with the NRS-2002. Therefore, we suggest that using the RFH-NPT improves the ability of clinicians to predict malnutrition risk in patients with cirrhosis primarily caused by hepatitis virus infection at an earlier stage.